1981
DOI: 10.1111/j.1600-051x.1981.tb02019.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study to compare the effect of stannous fluoride and chlorhexidine mouthrinses on plaque formation

Abstract: A clinical study was conducted on four adults to compare the relative efficacy of 0.2% chlorhexidine digluconate and 0.1% stannous fluoride (SnF2). Using a crossover experimental design, subjects rinsed twice daily for 5 days with SnF2 and then, after a 2-day interim recovery period, for 5 days with chlorhexidine. Statistically significant differences (P less than 0.05) in the relative efficacy of the two agents were found. Chlorhexidine was more effective in reducing Gingival and Plaque Indices, plaque wet we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…[2] Chlorhexidine (CHX) is the most studied and effective antiseptic for plaque inhibition and prevention of gingivitis when used twice daily as mouth rinse. [3] CHX besides its side effects including: Brown discoloration of the teeth, some restorative materials and mucosa; bitter taste and a slight increase in supragingival calculus formation is known as “Gold Standard” of antimicrobial rinses because of broad-spectrum activity and substantivity of 8–12 h.[45]…”
Section: Introductionmentioning
confidence: 99%
“…[2] Chlorhexidine (CHX) is the most studied and effective antiseptic for plaque inhibition and prevention of gingivitis when used twice daily as mouth rinse. [3] CHX besides its side effects including: Brown discoloration of the teeth, some restorative materials and mucosa; bitter taste and a slight increase in supragingival calculus formation is known as “Gold Standard” of antimicrobial rinses because of broad-spectrum activity and substantivity of 8–12 h.[45]…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of chlorhexidine in the plaque control in the early 70s, several alternative plaque inhibitors with clear-eut effect as compared with placebo have been tested (5)(6)(7)(8). However, when compared with chlorhexidine none has shown equal or better activity without also giving unacceptable side effects (9)(10)(11)(12). Also chlorhexidine has some unpleasant side effects restricting its general use (13)(14)(15).…”
mentioning
confidence: 99%
“…Studies have shown that CHX lack plaque inhibitory properties at lower concentrations. [ 16 ] Da Costa et al . [ 17 ] concluded that adjunctive use of CHX mouth rinse with mechanical SRP resulted in slightly greater PD reduction than did SRP alone.…”
Section: Discussionmentioning
confidence: 99%